Studying religions with the iron curtain closed and opened: the academic study of religion in Eastern Europe - Bubík, Tomáš; Hoffmann, Henryk (Studies in the history of religions, 2015)
Preface; List of Contributors; The Czech Journey to the Academic Study of Religions: From the Critique of Religion to its Study; Searching and Finding: A History of the Slovak Study of Religion; The Development of Religious Studies in Poland: History and the Present State; The History and Recent Trends of Religionswissenschaft in Hungary; Estonian Study of Religion: A Historical Outline of the 20th Century Developments; Development of the Study of Religion in Latvia in the 20th Century; The History of the Scientific Study of Religion and Current State of Religious Studies in Ukraine.